Analysis of Income Level of The Nipa Roofing Craftsman (Nypa fruticans Wurmb) in Kumai Subdistrict, Central Kalimantan - Gilang Maulana; Jumri Dulamin; Nursiah; Sari Mayawati; Eritha Kristiana Firdara (Talenta Publisher, 2023)
One of the efforts to increase income is utilizing non-timber forest products in the form of home industries. One of the non-timber forest products utilized by the community and have a business opportunity is the Nipa plant (Nypa fruticans Wurmb). It grows along rivers near estuaries to rivers with brackish water influenced by tides and is included in the mangrove/brackish forest type. The research aimed to analyze the utilization level of nipa (Nypa fruticans Wurmb), examine the income level of the nipa roof craftsman, measure the contribution level of the nipa roofing business to family income, and analyze the relationship between the income level and the utilization of nipa (Nypa fruticans Wurmb). Data was sampled using the census method. The respondents were the craftsmen of nipa roofs (only ten people were still active in making nipa roofs). The required data includes the utilization of nipa resource products, production costs, total revenue, selling price, income from the nipa roofing business, and income from other family members. The results showed that the total production of nipa palm roofs was 303,840/year. The average income of nipa roof craftsmen was Rp10,732,200/year. The income contribution of the nipa roof craftsmen to family income was medium (55%). The utilization of nipa forest resource products had a very strong and positive relationship in increasing the income of nipa roof craftsmen with a correlation value of 0.842.